Pengaruh Kinerja Keuangan terhadap Pertumbuhan Laba pada Perusahaan Perbankan BUMN yang terdaftar di Bursa Efek Indonesia - Nurasizah, Nurasizah; Samsinar; Nuraisyiah (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2024)
This research is a quantitative study that aims to determine whether there is an effect of financial performance on profit growth at State-Owned Commercial Banks (BUMN) listed on the IDX. The population of this study were Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), Bank Tabungan Negara (BTN), and Bank Mandiri (BMRI). The period of this study was taken from 2015-2022. Data collection was carried out using secondary data, namely documentation. The analysis technique used is the classical assumption test, multiple linear regression and hypothesis testing with the help of SPSS 26. The results of this study show that TATO financial performance does not have a significant influence on not have a significant influence on profil growth with a sig value of 0,795 and CAR financial performance does not have a significant influence on profil growth with a sig value of 0,939 and no simultaneous or joint influence between TATO and CAR on profil growth with a sig value of 0,899.